If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 2)(x + 2) + 4 = 32 Reorder the terms: (2 + x)(x + 2) + 4 = 32 Reorder the terms: (2 + x)(2 + x) + 4 = 32 Multiply (2 + x) * (2 + x) (2(2 + x) + x(2 + x)) + 4 = 32 ((2 * 2 + x * 2) + x(2 + x)) + 4 = 32 ((4 + 2x) + x(2 + x)) + 4 = 32 (4 + 2x + (2 * x + x * x)) + 4 = 32 (4 + 2x + (2x + x2)) + 4 = 32 Combine like terms: 2x + 2x = 4x (4 + 4x + x2) + 4 = 32 Reorder the terms: 4 + 4 + 4x + x2 = 32 Combine like terms: 4 + 4 = 8 8 + 4x + x2 = 32 Solving 8 + 4x + x2 = 32 Solving for variable 'x'. Reorder the terms: 8 + -32 + 4x + x2 = 32 + -32 Combine like terms: 8 + -32 = -24 -24 + 4x + x2 = 32 + -32 Combine like terms: 32 + -32 = 0 -24 + 4x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '24' to each side of the equation. -24 + 4x + 24 + x2 = 0 + 24 Reorder the terms: -24 + 24 + 4x + x2 = 0 + 24 Combine like terms: -24 + 24 = 0 0 + 4x + x2 = 0 + 24 4x + x2 = 0 + 24 Combine like terms: 0 + 24 = 24 4x + x2 = 24 The x term is 4x. Take half its coefficient (2). Square it (4) and add it to both sides. Add '4' to each side of the equation. 4x + 4 + x2 = 24 + 4 Reorder the terms: 4 + 4x + x2 = 24 + 4 Combine like terms: 24 + 4 = 28 4 + 4x + x2 = 28 Factor a perfect square on the left side: (x + 2)(x + 2) = 28 Calculate the square root of the right side: 5.291502622 Break this problem into two subproblems by setting (x + 2) equal to 5.291502622 and -5.291502622.Subproblem 1
x + 2 = 5.291502622 Simplifying x + 2 = 5.291502622 Reorder the terms: 2 + x = 5.291502622 Solving 2 + x = 5.291502622 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x = 5.291502622 + -2 Combine like terms: 2 + -2 = 0 0 + x = 5.291502622 + -2 x = 5.291502622 + -2 Combine like terms: 5.291502622 + -2 = 3.291502622 x = 3.291502622 Simplifying x = 3.291502622Subproblem 2
x + 2 = -5.291502622 Simplifying x + 2 = -5.291502622 Reorder the terms: 2 + x = -5.291502622 Solving 2 + x = -5.291502622 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x = -5.291502622 + -2 Combine like terms: 2 + -2 = 0 0 + x = -5.291502622 + -2 x = -5.291502622 + -2 Combine like terms: -5.291502622 + -2 = -7.291502622 x = -7.291502622 Simplifying x = -7.291502622Solution
The solution to the problem is based on the solutions from the subproblems. x = {3.291502622, -7.291502622}
| 6y-2(y-2)+6= | | 5x^2-17x+10=0 | | u+6u-3=0 | | .666w+6=10 | | 7(z-3)+5z-1= | | 4+ax=17-bx | | 76=2u^2+12 | | 11-7x=10x+15 | | 2x+(3*2)=12 | | 6b+8=(-42) | | 2x+5=-72-9x | | 4x^2+30x+351=0 | | j=6 | | 0=y^2-72 | | -Y+5=36 | | 2d-5=3 | | 9x-65=6x-8 | | 133=3x^2+3x+1 | | 5-Y=36 | | -5(2p+2)-7=3(p+5) | | 3u^2-84=0 | | 4r+7-t=9 | | -n^2+11n+28=0 | | 173-2x=34x+21 | | 5X-5Y=36 | | 56=7v^2 | | 13-15-3= | | 4-3x=8-x | | .6-.2(4-x)=1.2 | | -n^2-11n+28=0 | | 13a+1-10a=5+a | | (5x+2)(5x-2)=1221 |